Effects of rich cannabidiol oil on behavioral disturbances in patients with dementia: A placebo controlled randomized clinical trial - Hermush, Vered; Ore, Liora; Stern, Noa; Mizrahi, Nisim; Fried, Malki; Krivoshey, Marina; Staghon, Ella; Lederman, Violeta E.; Bar-Lev Schleider, Lihi (Frontiers in Medicine, 2022)
Background: Almost 90% of patients with dementia suffer from some type of neurobehavioral symptom, and there are no approved medications to address these symptoms. Objective: To evaluate the safety and efficacy of the medical cannabis oil ‘Avidekel’ for the reduction of behavioral disturbances among patients with dementia. Methods: In this randomized, double-blind, single-cite, placebo-controlled trial conducted in Israel (ClinicalTrials.gov: NCT03328676), patients aged at least 60, with a diagnosis of major neurocognitive disorder and associated behavioral disturbances were randomized 2:1 to receive either ‘Avidekel’, a broad-spectrum cannabis oil (30% cannabidiol and 1% tetrahydrocannabinol: 295 mg and 12.5 mg per ml respectively; n=40) or a placebo oil (n=20) three times a day for 16 weeks. The primary outcome was a decrease, as compared to baseline, of four or more points on the Cohen-Mansfield Agitation Inventory score by week 16. Results: From 60 randomized patients (mean age, 79.4 years; 36 women [60.0%]), 52 (86.7%) who completed the trial (all eight patients who discontinued treatment were from the investigational group), there was a statistically significant difference in the proportion of subjects who had a Cohen-Mansfield Agitation Inventory score reduction of ≥4 points at week 16: 24/40 (60.0%) and 6/20 (30.0%) for investigational and control groups, respectively (χ2=4.80, P=.03). There was a statistically significant difference in the proportion of subjects who had a Cohen-Mansfield Agitation Inventory score reduction of ≥8 points at week 16: 20/40 (50%) and 3/20 (15%), respectively (χ2=6.42, P=.011). The ANOVA repeated measures analysis demonstrated significantly more improvement in the investigational group compared to the control group at weeks 14 and 16 (F=3.18, P=.20). Treatment was mostly safe, with no significant differences in the occurrence of adverse events between the two groups. Conclusion: In this randomized controlled trial, ‘Avidekel’ oil significantly reduced agitation over placebo in patients suffering from behavioral disturbances related to dementia, with non-serious side-effects. Further research is required with a larger sample size.